Influence of uniaxial bending on IGZO TFTs: A study of materials and device - Magalhães, Daniela Ramalho (2018)
In recent years flexible electronics have gained relevance with applications such as displays, sensors and wearables. In that regard, studying how flexible transistors behave under bending has become of major importance. This work aims to fabricate indium gallium zinc oxide (IGZO) Thin Film Transistors (TFT) with the best bendability possible, without any major changes in the production techniques already used in the industry. To understand the influence of the substrate on flexible devices, TFTs were fabricated on polyimide substrates using different thicknesses, down to 25 μm, with and without parylene encapsulation layers on top of the device stack. To determine the position of the neutral strain plane, nanoindentation measurements were performed on different device layers at IKTS-Fraunhofer, within BET-EU project. The delamination of the substrates is a critical step, especially for thinner substrates. The concept of “paper blade” was used in this project to improve the yield of the delamination process. Initial bending measurements, using a 75 μm thick substrate, showed that bending radii of 45, 25 and 15 mm do not permanently change the performance of the TFTs. Tensile bending measurements with a radius of 1.25 mm were also performed, revealing that the 75 μm thick substrate achieves critical failure in <500 cycles, while the thinner substrate (25 μm) could withstand almost 1000 cycles. The most common failure mechanism observed under tensile bending was the appearance of cracks in the oxide dielectric when in direct contact with the polyimide substrate. These cracks do not appear in regions where molybdenum gates were in contact with the substrate, hence the mismatch between the coefficient of thermal expansion of the substrate and the dielectric thin film were identified as the reason for failure. This work shows that, even with intrinsically rigid materials as oxides and metals, it is possible to obtain reliable flexible TFTs, provided that proper stack engineering is considered for their fabrication.